2011
DOI: 10.1016/j.jtcvs.2010.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Heparinized cardiopulmonary bypass circuits and low systemic anticoagulation: An analysis of nearly 6000 patients undergoing coronary artery bypass grafting

Abstract: The experience with this patient cohort including mostly low- to medium-risk patients with a relatively short cardiopulmonary bypass time indicates that coronary artery bypass grafting performed with heparin-coated circuits and reduced level of systemic heparinization is safe and results in a very satisfactory clinical course. No signs of clotting or other technical incidents were recorded.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 25 publications
1
28
0
Order By: Relevance
“…We decided not to use CPB as it usually requires full heparinisation and anticoagulation, which may have worsened bleeding and altered surgical operating conditions (7). Given its size and complexity, a CPB circuit would also not have permitted ongoing postoperative support.…”
Section: Discussionmentioning
confidence: 99%
“…We decided not to use CPB as it usually requires full heparinisation and anticoagulation, which may have worsened bleeding and altered surgical operating conditions (7). Given its size and complexity, a CPB circuit would also not have permitted ongoing postoperative support.…”
Section: Discussionmentioning
confidence: 99%
“…Recent data emerged from a large cohort study by Ovrum et al indicate that the routine use of heparin-coated CPB circuits combined with reduced systemic heparinization is safe and has encouraging clinical results, with low rates of morbidity and mortality, as in OPCAB surgery. They reported few postoperative complications, limited need for banked blood transfusions and short periods of postoperative ventilatory support [ 46 ] . However, other studies showed controversial results, indicating no bene fi t when using heparin-coated circuits [ 47 ] .…”
Section: Tubingmentioning
confidence: 99%
“…For normothermic CPB, a heparin-coated, minimal extracorporeal circulation (MECC) with a recommended activated coagulation time (ACT) target of 250 to 300 seconds was used. 8,9 CPB was instituted after the administration of 175 IU/kg of unfractionated heparin (UFH), which resulted in an ACT of 309 seconds. According to the authors' institutional protocol, tranexamic acid was administered as a bolus of 10 mg/kg, followed by a continuous infusion of 1 mg/kg/h during CPB (CPB duration ϭ 198 minutes, aortic cross-clamp time ϭ 146 minutes).…”
Section: Case Reportmentioning
confidence: 99%
“…Additionally, the miniaturized, heparin-bonded circuit of the MECC minimizes the contact of blood to artificial surfaces and air, resulting in fewer inflammatory and hemostatic abnormalities. 8,9,20 Although preoperative therapy with heparin is a well-known risk factor for acquired antithrombin deficiency, 21 the normal antithrombin activity measured on the day of surgery strongly argued against this hypothesis. Thus, HIT appeared the most plausible cause for the new occurrence of an LV thrombus despite its unusual manifestation in a patient with uneventful preoperative thromboprophylaxis with LMWH.…”
mentioning
confidence: 99%
See 1 more Smart Citation